Faktor-Faktor yang Berhubungan dengan Kepatuhan Pemeriksaan Triple Eliminasi pada Ibu Hamil di Wilayah Kerja Puskesmas Batujaya Kabupaten Karawang - Astuti, Dewi; Hasrida, Hasrida (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Triple Elimination is an effective effort to prevent the transmission of infectious infections, namely HIV, Syphilis and Hepatitis B, from pregnant women to their children, so that it can improve the welfare of mothers and children and reduce the risk of complications that can cause illness and disability. This study aims to determine the factors associated with compliance with triple elimination examinations in pregnant women in the working area of the Batujaya Community Health Center, Karawang Regency in 2024. The research method used is an analytical observational research design with a cross sectional approach. Data collection was carried out through interviews using a questionnaire with 58 pregnant women respondents who were selected using purposive sampling. Research results show that there is a significant relationship between knowledge and compliance of pregnant women regarding triple elimination examinations at the UPTD Puskesmas Batujaya with a value of 0.012 (p<0.05), there is a significant relationship between the age of pregnant women and compliance with triple elimination examinations at UPTD Puskesmas Batujaya obtained a significant level of 0.003 (p < 0.05), there was a significant relationship between the education of pregnant women and compliance with triple elimination examinations at UPTD Puskesmas Batujaya obtained a significant level of 0.002 (p < 0.05), and there was a significant relationship between maternal employment. Pregnant women with compliance with the triple elimination examination at the Batujaya Community Health Center UPTD obtained a significant level of 0.001 (p < 0.05). Conclusions from this research, it is important to increase pregnant women's knowledge, age, education and occupation in increasing the compliance of pregnant women in undergoing triple elimination examinations. It is hoped that this research can provide input for related parties in efforts to improve the health of pregnant women through a triple elimination screening program. Keywords: Knowledge, Obedience, Age, Education, Employment, Triple Elimination.  ABSTRAK Triple Eliminasi merupakan upaya yang efektif untuk mencegah penularan infeksi menular, yaitu HIV, Sifilis, dan Hepatitis B, dari ibu hamil ke anaknya, sehingga dapat meningkatkan kesejahteraan ibu dan anak serta mengurangi risiko komplikasi yang dapat menyebabkan kesakitan dan kecacatan. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan kepatuhan pemeriksaan triple eliminasi pada ibu hamil di wilayah kerja Puskesmas Batujaya Kabupaten Karawang tahun 2024. Metode penelitian yang digunakan adalah desain penelitian observasional analitik dengan pendekatan cross sectional. Pengumpulan data dilakukan melalui wawancara menggunakan kuesioner kepada 58 responden ibu hamil yang dipilih secara purposive sampling. Hasil Penelitian menunjukkan bahwa terdapat hubungan yang signifikan antara pengetahun dengan kepatuhan ibu hamil tentang pemeriksaan triple eliminasi di UPTD Puskesmas Batujaya dengan nilai 0,012 (p< 0,05), ada hubungan yang signifikan antara usia ibu hamil dengan kepatuhan pemeriksaan triple eliminasi di UPTD Puskesmas Batujaya diperoleh tingkat signifikan 0,003 (p < 0,05), ada hubungan yang signifikan antara pendidikan ibu hamil dengan kepatuhan pemeriksaan triple eliminasi di UPTD Puskesmas Batujaya diperoleh tingkat signifikan 0,002 (p < 0,05), dan ada hubungan yang signifikan antara pekerjaan ibu hamil dengan kepatuhan pemeriksaan triple eliminasi di UPTD Puskesmas Batujaya diperoleh tingkat signifikan 0,001 (p < 0,05). Kesimpulan dari penelitian ini adalah pentingnya peningkatan pengetahuan ibu hamil, usia, pendidikan, dan pekerjaan dalam meningkatkan kepatuhan ibu hamil dalam menjalani pemeriksaan triple eliminasi. Penelitian ini diharapkan dapat menjadi masukan bagi pihak terkait dalam upaya meningkatkan kesehatan ibu hamil melalui program pemeriksaan triple eliminasi. Kata Kunci: Pengetahuan, Kepatuhan, Usia, Pendidikan, Pekerjaan, Triple Eliminasi.